Model-based approach to dose optimization of lopinavir/ritonavir when co-administered with rifampicin - Zhang, Chao (Blackwell Science Inc, 2012)
AIMS: Rifampicin, a key component of antitubercular treatment, profoundly reduces lopinavir concentrations. The aim of this study was to develop an integrated population pharmacokinetic model accounting for the drug–drug interactions between lopinavir, ritonavir and rifampicin, and to evaluate optimal doses of lopinavir/ritonavir when co-administered with rifampicin. METHODS: Steady-state pharmacokinetics of lopinavir and ritonavir were sequentially evaluated after the introduction of rifampicin and gradually escalating the dose in a cohort of 21 HIV-infected adults. Intensive pharmacokinetic sampling was performed after each dose adjustment following a morning dose administered after fasting overnight. A population pharmacokinetic analysis was conducted using NONMEM 7. RESULTS: A simultaneous integrated model was built. Rifampicin reduced the oral bioavailability of lopinavir and ritonavir by 20% and 45% respectively, and it increased their clearance by 71% and 36% respectively. With increasing concentrations of ritonavir, clearance of lopinavir decreased in an E(max) relationship. Bioavailability was 42% and 45% higher for evening doses compared with morning doses for lopinavir and ritonavir, respectively, while oral clearance of both drugs was 33% lower overnight. Simulations predicted that 99.5% of our patients receiving doubled doses of lopinavir/ritonavir achieve morning trough concentrations of lopinavir > 1 mg l(−1) during rifampicin co-administration, and 95% of those weighing less than 50 kg achieve this target already with 600/150 mg doses of lopinavir/ritonavir. CONCLUSIONS: The model describes the drug–drug interactions between lopinavir, ritonavir and rifampicin in adults. The higher trough concentrations observed in the morning were explained by both higher bioavailability with the evening meal and lower clearance overnight.